Ozone impacts on vegetation in a nitrogen enriched and changing climate. (January 2016) - Mills, Gina; Harmens, Harry; Wagg, Serena; Sharps, Katrina; Hayes, Felicity; Fowler, David; Sutton, Mark; Davies, Bill
Abstract: This paper provides a process-oriented perspective on the combined effects of ozone (O3 ), climate change and/or nitrogen (N) on vegetation. Whereas increasing CO2 in controlled environments or open-top chambers often ameliorates effects of O3 on leaf physiology, growth and C allocation, this is less likely in the field. Combined responses to elevated temperature and O3 have rarely been studied even though some critical growth stages such as seed initiation are sensitive to both. Under O3 exposure, many species have smaller roots, thereby enhancing drought sensitivity. Of the 68 species assessed for stomatal responses to ozone, 22.5% were unaffected, 33.5% had sluggish or increased opening and 44% stomatal closure. The beneficial effect of N on root development was lost at higher O3 treatments whilst the effects of increasing O3 on root biomass became more pronounced as N increased. Both responses to gradual changes in pollutants and climate and those under extreme weather events require further study. Highlights: CO2 amelioration of O3 effects on leaf physiology are less likely in the field. Both extremes of temperature and O3 impact on critical growth stages. Many species are more sensitive to drought as a result of exposure to O3 pollution. The beneficial effect of N on root development is lost at higher O3 treatments. The effects of O3 on root biomass are higher at high than low N. Abstract : A process-oriented perspective on the combined effects of ozone, climate change and/or nitrogen on vegetation.